Implementation of Business Strategies through Organization Design Concept at PT. Sarimelati Kencana Tbk (PZZA) - Humairoh, Humairoh; Wahyu Setyawati, Novita; Wijayanti, Murti; Anggoro, Wahyu; Parluhutan, Bobby (Dinasti Publisher, 2022)
The spread of the global pandemic has an impact on the slow pace of development in several industrial sectors, including PT. Sarimelati Kencana, Tbk. is engaged in the culinary sector with the flagship brand Pizza Hut. The company is known as a restaurant that provides Italian-American cuisine in the form of pasta, side dishes, and desserts. The purpose of this paper is to analyze how PZZA implements its business strategy through the concept of organizational design based on the results of the 2020 EGMS to achieve a market position in this new normal era. This writing uses explanatory research with a qualitative approach, with the SWOT Analysis method and the Canvas Business Model. The business strategy used by Pizza Hut (PZZA) is to stay afloat in the face of the impact of a decline. In. people's. purchasing. power. Efforts that can.be made by PZZA are implemented in several business strategies, including redesigning the company's organizational concept through modification of the organizational structure as a supporter of culture within the company, as well as continuing to carry out internal control activities.